Abstractionism - WILL, RALF G (IJRDO - Journal of Social Science and Humanities Research, 2020)
In aid of my new THEORY OF ART, I painted two situations in more detailed colours. I also highlighted something abstract, indeterminate, fuzzy, peeled off as an essential angle of creativity. Some grandmastersof Abstraction have become classix of Art. Here is a recap of above abstract incidents: